Investigation on Pore-Fracture of Coal and Its Influence Mechanism on Tensile Failure Behavior of Coals with Bursting Proneness - Yutao Li; Qingwei Guo; Xunchen Liu; Yaodong Jiang; Bo Zhang; Hao Wang (Geofluids)
Both computed tomography (CT) and notched semicircular bend (NSCB) tests are performed for coals with high and medium bursting proneness to extract the scientific expression of pore-fracture and its influence mechanism on the tensile failure behavior. The acoustic emission (AE) parameters in the sample during loading and failure are monitored, and the influence mechanism of pore-fracture on tensile failure behavior of coal is analyzed. The result illustrates that the spatial distribution feature of the pore-fracture in coals with high and medium bursting proneness is extremely different. The deformation and failure mode of the coals are affected by many factors, loading mode, notch depth and width, mechanical properties of matrix and minal, spatial distribution feature of pore-fracture, etc. The influence of primary pore-fracture in the coal on the extension and penetration of the secondary fracture could be divided into two types: bifurcation and promotion, which would cause different local damage in the sample and affect the final failure mode. The feature of acoustic emission parameters indicates that the deformation and failure process of a sample under loading could be divided into four stages: compaction stage, elastic deformation stage, displacement plastic growth stage, and post peak failure stage, which is the result of comprehensive action of many factors. The evolution process of secondary fracture is accompanied by the dissipation of elastic strain energy and the intensification of internal damage of coal, which reflects the failure process of coal.